Phycoremediation of Cadmium using Chlorella vulgaris in Photobioreactor - Anca Awal Sembada; Teguh Adhitia Suyadi (Bioeksperimen: Jurnal Penelitian Biologi, 2023)
Chlorella vulgaris had the ability to accumulate heavy metals in their bodies, so they could be used as biosorbent in handling heavy metal pollution in waters. The effectiveness of C. vulgaris in the remediation of cadmium (Cd) would be tested in this present study. C. vulgaris were cultured for 14 days in the photobioreactor which was an enclosed chamber that was fully aerated and illuminated with LED lamps. Cadmium with concentrations of 0 (control), 0.05, and 0.1 ppm was mixed with C. vulgaris growth medium. The number of C. vulgaris cells was counted every 3.5 days using a hemocytometer to determine the growth condition. Metal concentrations were also measured on days 0, 7, and 14 using atomic absorption spectrophotometry (AAS). C. vulgaris was able to reduce cadmium levels up to 98%. The decrease in cadmium levels with the highest efficiency occurred at a cadmium concentration of 0.05 ppm.